Odessa-512: Hybrid New Hash Function - Mr. Touraj Ostovari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Nowadays, security is an important matter in all computer fields. The presence of computers of different sizes in our lives has multiplied the importance of this subject. For example, the security problem of MD5 [1] is not negligible, and it must be replaced with a new hash algorithm as soon as possible. A lower computational speed is one of the major issues of the hash algorithm of this study because we used multiple other hash algorithms to prevent collisions alongside the BEL [2] algorithm for creating random bits and the divide and conquer method for moving and dividing the bit blocks during the calculations. This hashing model completely solves the common collisions in MD5 and SHA1 [3], which we will discuss later on. This model is on par with Keccak-512 and Blake-512 in terms of the Avalanche effect. Also, the TMTO and Birthday attacks [4] were implemented on this model, and it successfully passed the no collision security test.